Gas Detector (Chloroflourocarbons. CFCs) / Asmah Shaharudin and Rafidah Abdul Rahman - Shaharudin, Asmah; Abdul Rahman, Rafidah (2003)
Final project is part of our course, structure that needs to be taken to complete our Diploma, by a student that is in the final years. This project has been required to finish in two semesters, which the first project (KEU280) is taken while in semester 05 and continued in second project (KEU 380) in semester 06. The main propose that all electronics students have to take this course is to give us opportunity to test our skill and to gather all the knowledge that we have been studying for this few years. From this kind of course, we can learn the practical way of doing the project such as design, drawing, experimenting, prototyping, testing and troubleshooting. We also can figure out the best way to improve our knowledge for the purpose of using in the future. Nowadays, the rapid changes in quality of life require new technologies to fix with us. It is important to design new system that can make everything simpler as possible to operate. We choose this project because we always heard from a previous time about the depletion of ozone layer. The depletion of ozone layer will give an effect on our environment that it can increase the temperature of environment and it will cause a skin cancer. This project is called a ‘Gas Detector (CFCs)’. Due to the rapid increase in the use of refrigerants, in homes and automobiles, it is critical that everyone keep his or her air-conditioning system and refrigerators in good repair. Finding any possible refrigerant leaks is a must. The circuit described here will sniff out gas leaks. It uses a variable frequency oscillator system that emits a low-frequency audio tone when exposed to clean air but a higher tone when gas is detected by its unique, but readily available, TGS830 sensors. Six alkaline cells or 9-to-12V-power supply can power it.